Profiles of the Prophet’s Companions as Guardians of Quranic Memorization and Transmission - Muhammad Numan; Ahmad Hamed; Fathiyah Mohd Fakhruddin (Journal of Theory and Research Memorization Quran, 2025)
This study examines the role of the Prophet Muhammad’s companions who memorized the Quran in safeguarding revelation and shaping the intellectual tradition of Islam, emphasizing their contributions to oral transmission, written documentation, and the establishment of pedagogical models that remain central to Islamic education. Employing a literature review of classical sources (kutub al-turath) and contemporary scholarship on Quranic codification, the research highlights figures such as Ubay ibn Ka‘ab, Abdullah ibn Mas‘ud, Zayd ibn Thabit, and Ali ibn Abi Talib, who were recognized as leading authorities in Quranic memorization and teaching. These companions exemplified the integration of linguistic intelligence, spiritual devotion, and commitment to revelation, mastering the Quran comprehensively while verifying recitations, educating the tabi‘in generation, and contributing to the compilation of the mushaf during the caliphate of Usman ibn Affan. Their profiles demonstrate how memorization and teaching ensured the integrity and unity of the Quran across diverse communities. The findings affirm that Quranic memorization has strong historical roots and remains a cornerstone of Islamic pedagogy, scholarship, and spiritual practice, linking early preservation efforts with contemporary educational traditions and underscoring its enduring significance in both spiritual life and intellectual heritage.